Fine mapping and candidate gene mining of major QTL QSL.caas-6BL.1 for spike length in bread wheat (Triticum aestivum L.) - Xie, Xiaohan; Meng, Xianghua; Ren, Kangzhen; Cui, Yutao; Zhang, Wenjiao; Xu, Dengan; Ma, Wujun; Dai, Xuehuan (Frontiers in Plant Science, 2026)
BackgroundSpike length (SL) is a key agronomic determinant of wheat spike architecture and yield potential. This study focused on fine‑mapping a major SL‑regulating quantitative trait locus (QTL), QSL.caas‑6BL.1, previously identified in a Doumai (DM) × Shi 4185 population.MethodsHigh‑density molecular markers were developed and used to screen recombinant families derived from the cross. Genotype–phenotype co‑segregation analysis in advanced generations was employed to delineate the QTL region.ResultsThe QSL.caas‑6BL.1 locus was delimited to a 3 Mb physical interval on chromosome 6B (IWGSC RefSeq v2.1). Gene annotation and transcriptome analysis of young spikes identified 25 high‑confidence genes within this region. Among these, the NAC transcription factor gene TraesCS6B03G1211800 emerged as the prime candidate, being the only gene that combined significant differential expression between parental near‑isogenic lines with coding‑sequence variants leading to amino acid changes.ConclusionOur work narrows a major QTL to a precise genomic interval and pinpoints a promising candidate gene, providing a valuable resource for understanding the genetic control of wheat spike development and for marker‑assisted breeding.